Guidelines for investigating officer-involved shootings, arrest-related deaths, and deaths in custody - Ross, Darrell L. (Darrell Lee), 1951-; Vilke, Gary M., 1966- (Routledge, 2017)
As unrest over officer-involved shootings and deaths in custody takes center stage in conversations about policing and the criminal justice system, Guidelines for Investigating Officer-Involved Shootings, Arrest-Related Deaths, and Deaths in Custody addresses critical investigation components from an expert witness perspective, providing the insights necessary to ensure a complete investigation. Investigating a custodial death or an officer involved in a shooting presents unique and complex issues: estate, community, judicial, agency, involved officer, and public policy interests are all at stake. These types of deaths present various emerging medical, psychological, legal and liability, technical, and investigatory issues that must be addressed through a comprehensive investigation. This book is ideal for students in criminal investigation, death investigation, crime scene investigation, and special topic courses in custodial deaths and officer-involved shootings, as well as for death investigators, law enforcement officers, police administrators, and attorneys. --